The use of molecular genetic technologies for the implementation of sports selection and provision of training-competitive process in rowing - Zukow, Walery; Kozyrev, Andrey; Gozhenko, Anatoliy (Quality in Sport, 2017)
The question of the promise of application of molecular genetic technologies in rowing sports is considered. The main directions that can be used for sports orienteering and selection, and after their completion, are provided for providing high-level training-competitive process at the level of the sport.